2016
DOI: 10.18203/issn.2454-5929.ijohns20164786
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized middle turbinate mucoperiosteal flap in skull base defects: follow-up analysis of 20 cases

Abstract: <p class="abstract"><strong>Background:</strong> Vascularized flaps are preferred in repair of skull base defects since they provide quality tissue volume and allow rapid healing. Though nasoseptal flap is the gold standard it may not be available always and has its own share of pitfalls; this makes the middle turbinate flap a viable alternative. This descriptive study was designed to analyze the efficacy of middle turbinate flap in endoscopic closure of skull base defects and to define indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…This coincided with George et al (16) who revealed that the most common clinical presentation in middle turbinate flap intervention group was unilateral watery nasal discharge (n=13[65%]). Of these 10 patients had spontaneous CSF rhinorrhea while 3 had history of trauma.3 patients presented as recurrent meningitis, 2 following trauma and 1 after spontaneous CSF rhinorrhea.…”
Section: Discussionsupporting
confidence: 85%
“…This coincided with George et al (16) who revealed that the most common clinical presentation in middle turbinate flap intervention group was unilateral watery nasal discharge (n=13[65%]). Of these 10 patients had spontaneous CSF rhinorrhea while 3 had history of trauma.3 patients presented as recurrent meningitis, 2 following trauma and 1 after spontaneous CSF rhinorrhea.…”
Section: Discussionsupporting
confidence: 85%
“…To date, use of MTFs for the reconstruction of skull base defects in patients has been reported in seven studies with a combined total of 51 patients. [48][49][50][51][52][53][54] All but one reported case were considered successful and were without long-term CSF leaks, infection, pneumocephalus, or significant crusting. The one incidence of MTF failure was due to a necrotic MTF following a failed NSF.…”
Section: Mtf Outcomesmentioning
confidence: 99%
“…The one incidence of MTF failure was due to a necrotic MTF following a failed NSF 51 . Other reported complications include one patient who had transient CSF leakage during the immediate postoperative period that subsided fully, a patient in which an MTF was insufficient to covered the defect, and another in whom an MTF was irreparably torn during the operation 48,54 …”
Section: Intranasal Vascular Pedicled Flapsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the patients in their study were operated on for either pituitary macroadenoma, or arachnoid cyst, or Rathke's cleft cyst. George et al(16) reported 100% success rate with MT flap reconstruction in their study of 20 patients. All their patients had small to medium sized defects.…”
mentioning
confidence: 96%